Kontribusi Pengalaman Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Fatmaliza Fatmaliza; Syamsir Syamsir; Jumiati Jumiati (Journal of Education on Social Science (JESS), 2018)
The objective of this research was to know the influence of work experience on the performance nagari apparatus in managing nagari finance in Tanah Datar Regency. The problem of this research is that some apparatus of nagari in this regency did not have sufficient work experience in financial management. The population in this research was all nagari apparatus totaling 525 people. Sample in this research determined through random sampling technique and consisted of 227 nagari apparatus from 32 nagaris. Data in this research collected through questionnaire with Likert scale measurement. The data were analyzed using multiple linear regression. The results of this research showed that there were influence of work experience on performance of nagari apparatus in financial management in Tanah Datar Regency. The results of the partial test showed that the influence of work period variable (X 1) on the performance of the nagari apparatus was 7.9%, the influence of the level of knowledge and skills (X 2) towards the performance of the nagari apparatus amounted to 8.8%, and the influence of mastery against the work and equipment (X 3) on the performance of the nagari apparatus in financial management was 9.3%. While the simultaneous influence of these three variables (X1, X2, and X3) on the performance of the nagari apparatus was 11.2%.